PENGEMBANGAN E-LKPD VIRTUAL FIELD TRIP TOPIK HIDROPONIK BERBASIS EDS BERORIENTASI LITERASI NUMERASI DI SEKOLAH DASAR - Asri Astuti, - (2022)
Learning tools are needed in teaching and learning activities to support a learning goal. One of the learning tools needed is the Student Worksheet. This research is a research that develops learning tools in the form of E-LKPD Virtual Field Trip based on ESD which is oriented towards literacy and numeracy. By using electronic-based worksheets, of course, learning will be more interesting for students, they can learn independently and can do it anytime and anywhere with learning focused on literacy and numeracy competencies. The purpose of this study is to describe the initial design of learning device development products in the form of E-LKPD, describe the results of the E-LKPD trial and produce final draft of E-LKPD. Then the E-LKPD is equipped with a Virtual Field Trip with the topic of hydroponics. The research method used is Design Based Research (DBR). The results of the study found that the E-LKPD development product was feasible to use with several improvements that had been made by researchers, in accordance with the direction of validators who were experts in the fields of material, design and pedagogy. So, with improvements to the product design, an electronic ESD-based Student Worksheet with literacy and numeracy orientation was produced which was declared valid by experts and deserved to be tested on fourth grade elementary school students.